Tehnologije toplotnih črpalk - Halozan, Hermann (Strojniški vestnik, 2000)
Mankind presently has serious problems, the growth of the population primarily in the developing countries, the expected climate change due to polluting the atmosphere with CO2 from burning fossil fuels and other greenhouse gases, and ozone depletion. Heat-pumping technologies, i.e. refrigeration, air conditioning, and heat pumps, more or less unknown and hardly recognised by the public, have the potential for reducing the negative effects resulting from these boundary conditions. But the public awareness of these technologies has to be improved. Heat-pumping technologies are reliable, energy efficient, and environmentally friendly, they are in use world wide and the turn-over of the related industry is only 10% less than the turn-over of the automotive industry. Heat pumping is one of the key technologies required to achieve the targets set at the Kyoto summit.
Keywords: črpalke toplotne; razvoj črpalk; hladiva; vplivi na okolje; hladilni sistemi; toplotne črpalke